Gender Mediation Discourse and the Prospect of Sustainable Peace in Nawal El Saadawi’s The Hidden Face of Eve: Women in the Arab World - Damlègue, LARE (International Journal of Language and Literary Studies, 2025)
The objective of this article is to analyse Nawal El Saadawi’s critical ideas regarding gender mediation in The Hidden Face of Eve: Women in the Arab World. It is to show how she negotiates discourse to encourage dialogue between men and women to construct a balanced society that encourages participatory development. It specifically explores her ideas that level criticism against the unjust/inhuman treatment of women in the Egyptian society thereby calling for a change of attitude towards women, aiming to end sexism, oppression and exploitation of women by patriarchy. As methodological and theoretical approaches, the study is a textual analysis sustained by an African Feminist critical approach developed by Molara Ogundipe-Leslie and Flora Nwapa.